Answer:
Step-by-step explanation:
f(x)=-4x+2
g(x)=x²+1
(gof)(x)=g(f(x))=g(-4x+2)=(-4x+2)²+2=16x²-16x+4+2=16x²-16x+6
(gof)(3)=16(3)²-16(3)+6=144-48+6=150-48=102
Answer: the link you posted is the area of the shape
Step-by-step explanation:
Answer:
5
Step-by-step explanation:
First, find the equation of the line:
put it in the form y = mx + b where m is the slope and b is the y-intercept
You already have m = 2, so y = 2x + b.
Then, since you know (1, 3) is a solution so you can plug x = 1 and y = 3 into the equation to find out what b is.
3 = 2 * 1 + b
3 = 2 + b
1 = b
This means the equation of the line is y = 2x + 1.
Then, since you're trying to find out what y is when x = 2, you can plug in x = 2 into the equation:
y = 2 * 2 + 1
y = 4 + 1
y = 5
5 is the answer
Answer:
x = 21
Step-by-step explanation:
11x – 32 = 31 + 8x
11x = 63 + 8x
3x = 63
x = 21